Longitudinal analysis of memory Tfh cells and antibody response following CoronaVac vaccination - Pengcheng Zhou; Cheng Cao; Tuo Ji; Ting Zheng; Yaping Dai; Min Liu; Junfeng Jiang; Daoqi Sun; Zhonghu Bai; Xiaojie Lu; Fang Gong (JCI Insight, 2023)
The inactivated vaccine CoronaVac is one of the most widely used COVID-19 vaccines globally. However, the longitudinal evolution of the immune response induced by CoronaVac remains elusive compared with other vaccine platforms. Here, we recruited 88 healthy individuals who received 3 doses of CoronaVac vaccine. We longitudinally evaluated their polyclonal and antigen-specific CD4+ T cells and neutralizing antibody response after receiving each dose of vaccine for over 300 days. Both the second and third doses of vaccine induced robust spike-specific neutralizing antibodies, with a third vaccine further increasing the overall magnitude of antibody response and neutralization against Omicron sublineages B.1.1.529, BA.2, BA.4/BA.5, and BA.2.75.2. Spike-specific CD4+ T cells and circulating T follicular helper (cTfh) cells were markedly increased by the second and third dose of CoronaVac vaccine, accompanied by altered composition of functional cTfh cell subsets with distinct effector and memory potential. Additionally, cTfh cells were positively correlated with neutralizing antibody titers. Our results suggest that CoronaVac vaccine–induced spike-specific T cells are capable of supporting humoral immunity for long-term immune protection.